Degradation of pentachlorophenol by a Flavobacterium species grown in continuous culture under various nutrient limitations. - Topp, E (1990)
A Flavobacterium sp. was grown in continuous culture limited for growth with ammonium, phosphate, sulfate, glucose, glucose + pentachlorophenol (PCP) (0.065 h -1), or PCP. Cells ere harvested, washed, and suspended to 3 x 10(7) cells ml (-1) in shake flasks containing a complete mineral salts medium without added carbon or supplemented with 50 mg of PCP ml(-1) or 50 mg of PCP ml(-1) + 100 mg of glucose ml(-1). The PCP concentration and the viable cell density were determined periodically. Cells that were grown under phosphate, glucose, or glucose + PCP limitation were more sensitive to PCP and took longer to degrade 50 mg of PCP ml(-1) than did cells that very were grown under ammonium, sulfate, or PCP limitation. Glucose stimulated viability and PCP degradation in all cases except when the cells were grown under carbon limitation with glucose and PCP added together as the carbon source. These results indicate that there is a relationship between nutrient limitation, phenotypic variation, and the sensitivity to and degradation of PCP by this organism.